Reconstruction of Deep Learning-Based Islamic Religious Education (PAI) Learning in Realizing a Love-Based Curriculum. - Dudiyono Dudiyono (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Islamic Religious Education (Pendidikan Agama Islam/PAI) plays a strategic role in shaping students’ character, morality, and spirituality amidst increasingly complex social changes. The transformation of PAI learning needs to be directed toward a more profound, humanistic, and meaningful learning process. This study employed a qualitative approach. The findings reveal that deep learning serves as an educational approach capable of encouraging students to understand Islamic teachings reflectively, critically, and contextually, so that religious learning is not merely oriented toward memorization and cognitive achievement, but also toward the internalization of values in everyday life. Meanwhile, the love-based curriculum emerges as a new educational paradigm emphasizing the values of compassion, empathy, tolerance, and respect for humanity as the primary foundations of the learning process. In the context of PAI, these values are aligned with Islamic teachings that uphold the concept of rahmatan lil ‘alamin and the development of noble character. The integration of deep learning and a love-based curriculum is able to create PAI learning that not only develops students’ intellectual intelligence, but also fosters spiritual awareness, social concern, and holistic humanistic character. Therefore, the reconstruction of PAI learning through the deep learning approach and love-based curriculum becomes a strategic step in presenting Islamic education that is more relevant, inclusive, transformative, and capable of addressing the challenges of modern life.